Cake-Eating with Private Information - Reyer Gerlagh; Matti Liski (Center for Economic Studies and ifo Institute (CESifo), 2014)
We consider a model of cake-eating with private information. The model captures phenomena such as trust and security of supply in resource-use relationships. It also predicts supply shocks as an equilibrium phenomenon: privately informed sellers have incentives to reveal resource scarcity too late, through a supply disruption, after which they exploit the consumers' inability to immediately adjust demand. Two puzzles that a standard exhaustible-resource theory cannot explain are resolved: sellers have an incentive to overstate their resources rather than emphasize scarcity, and consumers can switch to alternatives before exhausting the resource thereby leaving socially valuable resource in the ground.
Keywords: D40; D90; O33; Q40; 330; exhaustible resources; asymmetric information; resource dependence